Perpetual peace : essays on Kant's cosmopolitan ideal - Bohman, James; Lutz-Bachmann, Matthias (Studies in contemporary German social thought., 1997)
In 1795 Immanuel Kant published an essay entitled "Toward Perpetual Peace: A Philosophical Sketch". In the essay, Kant argues that it is humankind's immediate duty to solve the problem of violence. The essays in this text argue that history has both confirmed and outstripped Kant's prognoses.